371 Insomnia and Metacognitive abilities: a new treatment target?. (3rd May 2021) - Sforza, Marco; Scarpellino, Alessandro; Salibba, Andrea; Galbiati, Andrea; Zucconi, Marco; Casoni, Francesca; Ferini-Strambi, Luigi; Castronovo, Vincenza
Abstract: Introduction: Metacognition is defined as the ability to reflect on one's mental state. Literature showed that dysfunctional metacognitive activity (such as worry and rumination) plays an important role in insomnia genesis and maintenance. The aim of this study is (i) to evaluate metacognition differences between insomnia disorders (ID) patients and good sleepers (GS)and (ii) to assess Cognitive-Behavioral Therapy for Insomnia (CBT-I) effectiveness on both insomnia and metacognitive abilities. Methods: We compared 27 GS (Insomnia Severity Index, ISI<10) (63.0% female, mean age 33±13.7yrs) and 27 ID patients (51.9% female, mean age 46.4±13.7yrs) evaluated both by ISI and Metacognition Insomnia Questionnaire (MCQ-I). ID patients underwent 7-session of group CBT-I and were evaluated pre- (T0) and post- (T1) treatment. Results: GS and ID patients differed in MCQ-I total score (GS=105.6±20.5 vs ID= 138.1±26.2). All ID patients' scores were above the clinical cutoff of 110. ID patients showed significant improvements both at ISI (T0=14.67±4.67 vs T1=7.07±4.37, p<0.001) and Sleep Diary parameters (T0 vs T1, p<0.05) as sleep latency, wake after sleep onset and sleep efficiency at T1. ID patients also showed an improvement of MCQ-I scores at T1, nevertheless, maintaining MCQ-I the mean score above the clinical cutoff level (MCQ-I_T0=138.1±26.2 vs MCQ-I_T1=123.7±28.6; p<0.05). Indeed, 29.6% of ID patients maintained equal or worse MCQ-I score at T1 compared to T0; 63% of ID patients still had a MCQ-I score above the clinical cutoff at T1. Conclusion: CBT-I results effective on insomnia symptoms. Metacognitive dysfunctions appears to be a core feature in ID patients compared to good sleepers. Although the score reduction was significant after CBT-I, metacognitive dysfunction did not show remission after treatment possibly indicating the need of a specific intervention on this aspect. Metacognitive dysfunction in ID needs to be further investigated and may represent a new treatment target, in order to improve CBT-I effectiveness. Support (if any): None